PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII SMPN 2 TILATANG KAMANG - Windiani, Weni (Jurnal Edukasi dan Penelitian Matematika, 2024)
In order for students to think more critically and analytically, they need to hone their mathematical skills in the form of problem solving. However, the abilitiesof class VII students of SMPN 2 Tilatang Kamang are still low, it is caused they have not been actively in learning. The Student Teams Achievement Division (STAD) model, a collaborative learning strategy, was implemented to address the problem. This study wanted to see how students' ability in solving mathematical problems improved with the introduction of the STAD learning model. In addition, it was also to find out whether the STAD model improved students' ability to solve mathematical problems better than the traditional learning paradigm. Descriptive and quasi-experimental methodologies were used in this study, with a posttest-only non-equivalent control group design. All the seven grade students of SMPN 2 Tilatang Kamang in 2023/2024 academic year were the research population. With , the P-value =0,029 is obtained, it meant that the P-value , so that the  is rejected. The research result showed that the students with the STAD Model have better mathematical problem solving skill than students with conventional learning model and students’ problem solving skill was increased after implementing the STAD Cooperative Learning Model.Keywords– Conventional Learning , Problem Solving Ability, Student Teams Achievement Division